A Regulatory Role of the Bateman Domain of IMP Dehydrogenase in Adenylate Nucleotide Biosynthesis - Pimkin, Maxim (American Society for Biochemistry and Molecular Biology, 2009)
The Bateman domain (CBS subdomain) of IMP dehydrogenase (IMPDH), a rate-limiting enzyme of the de novo GMP biosynthesis, is evolutionarily conserved but has no established function. Deletion of the Bateman domain has no effect on the in vitro IMPDH activity. We report that in vivo deletion of the Bateman domain of IMPDH in Escherichia coli (guaB(ΔCBS)) sensitizes the bacterium to growth arrest by adenosine and inosine. These nucleosides exert their growth inhibitory effect via a dramatic increase in the intracellular adenylate nucleotide pool, which results in the enhanced allosteric inhibition of PRPP synthetase and consequently a PRPP deficit. The ensuing starvation for pyrimidine nucleotides culminates in growth arrest. Thus, deletion of the Bateman domain of IMPDH derepresses the synthesis of AMP from IMP. The growth inhibitory effect of inosine can be rescued by second-site suppressor mutations in the genes responsible for the conversion of inosine to AMP (gsk, purA, and purB) as well as by the prsA1 allele, which encodes a PRPP synthetase that is insensitive to allosteric inhibition by adenylate nucleotides. Importantly, the guaB(ΔCBS) phenotype can be complemented in trans by a mutant guaB allele, which encodes a catalytically disabled IMPDH(C305A) protein containing an intact Bateman domain. We conclude that the Bateman domain of IMPDH is a negative trans-regulator of adenylate nucleotide synthesis, and that this role is independent of the catalytic function of IMPDH in the de novo GMP biosynthesis.